IMPROVING LIBRARY CUSTOMER SATISFACTION THROUGH THE IMPLEMENTATION OF THE SMILE AND GREET CAMPAIGN - Akmal Sutja; Robi Hendra; Rio Dezaneru; Mohamad Muspawi; Yantoro Yantoro (Dinasti International Journal of Education Management And Social Science, 2021)
The ability of library staff in building visitors’ trust and assurance determines customer satisfaction and service quality. The purpose of this research is to find out the improvement of customer satisfaction through the application of smiling and greeting in circulation service at the library of Jambi University. This research is a service action research. The subjects were 30 students of Jambi University. This research was conducted in two cycles, using steps in action research which included planning, action, evaluation and reflection. This research was conducted collaboratively between researchers as observers and library staff as service providers. Data collection techniques used in this study include questionnaires, observations, interviews, and check lists. The result of this study obtained the percentage of customer satisfaction before the implementation of service is 48% with a moderate level, then increased by 17% to 67% with a high level in the first cycle and in the second cycle increased by 14% to 81% which is the highest level achieved due to morning greetings with hands folded in front of the chest, smiling teeth and small talks that ask questions related to customers’ personal.